MENGUKUR LOYALITAS KONSUMEN MELALUI EKUITAS MEREK PADA PRODUK KOSMETIK - Tuti Mulyani; Asep Muhamad Ramdan; Acep Samsudin (JURNAL EKOBIS DEWANTARA, 2020)
The purpose of this study is to measure how much influence brand equity has on consumer loyalty. The variables in this research are brand awareness (X1), perceived quality (X2), brand association (X3), brand loyalty (X4) and consumer loyalty (Y). The method used is quantitative research methods with an associative approach by spreading to 150 female respondents aged 25-35 years. Consumer loyalty is influenced by brand equity while others are influenced by other variables examined in this study. There is a relationship between the Brand Equity dimension to Consumer Loyalty. Of the overall brand equity variables, there is one variable that has no effect and is not significant on consumer loyalty, namely perceived quality and the most influential on consumer loyalty is brand loyalty.